مقارنة بين زوايا الميل للألواح الشمسية الثابتة لمدينة بغداد باستخدام جهاز محلل الظل للإشعاع الشمسي على مدار سنة كاملة - كاظم عماد جواد (University of Thi-Qar Journal of Science, 2014)
Generated energy by fixed solar panels depended on the optimum tilt angle with the horizon, so it must be defined correctly to improve the performance of the solar panel system. In this research the values of optimum tilt angle with the horizon of solar panels for Baghdad city was calculated monthly and quarterly and annually by using shadow analyzer of solar radiation. The optimum tilt angles is (60.51, 37, 19.5, 0, 0.13, 30, 45.55 , 60) degrees monthly, respectively and quarterly is 58 ° for months (12, 1, 2) and 19 degrees for months (3, 4, 5) and 2 degrees for months (6, 7, 8) and 45 degrees for months (9, 10, 11 ) When dividing the year into two seasons the optimal angle is 13 degrees for months (4, 5, 6, 7, 8, 9) and 51 degrees for months (10,11, 12, 1, 2, 3). The annual optimum tilt angle is 30 degrees it is noticed an increase in optimum tilt angle in winter than in summer and that is because of the increasing in the sun declination and the decreasing in the number of noon hours in winter. The increasing in the amount of energy falling on the solar panels was 8.34% when the tilt angle changed monthly and 6.85% when it changed quarterly and 6.61% when it changed for two seasons with respect to yearly fix tilt angle.